INTERVENTIONS TO REDUCE PAIN IN STROKE PATIENTS - Utami, Vidya Tyagita; Chayati, Nur (Universitas Aisyah Pringsewu, 2024)
Background:Pain is a sensory experience caused by tissue damage. In stroke patients pain occurs due to paralysis or weakness where stroke patients can experience paralysis in the muscles so that it can cause pain. This study conducted a literature review on various interventions that can reduce pain in stroke patients.Objective:This literature review aims the latest information about interventions that are effective in reducing the pain of stroke patients. Method: The research method uses PRISMA with a systematic approach and selection process. Library sources are searched online databases such as PubMed, Scopus, and Ebsco. The selected articles include reputable journals published in Indonesian and English. Result: After carrying out a screening process using PRISMA, 6 articles were found that were relevant and worthy of review. Based on a journal review, the results show that there are various types of interventions that are effective in reducing pain in stroke patients, including the use of drugs such as analgesics, then physical therapy such as traditional Thai messaging and shoulder management. Apart from that, there are non-pharmacological interventions such as providing functional electrical stimulation, kinesio tapping and dry needling therapy which can help reduce pain. This research can also provide important information for health workers in providing appropriate interventions to reduce pain in stroke patients. However, further research is needed to identify the most effective interventions in reducing pain in stroke patients.